UTAUT Model: Approach to the Use and Acceptance of Halal Information System (SIHALAL) in Small and Medium Food Businesses in the Solo Raya Area - Wagiyem, Wagiyem; Sudarmadi, Sudarmadi; Putri, Rani Cahyaning (Jurnal Maksipreneur, 2025)
The study aims to empirically investigate the UTAUT model, which encompasses performance expectations, effort expectations, social influence, facilitating conditions, interest in using a system, and its impact on the use of information systems. All food sector SMEs in Solo Raya are the population in this study. The sampling method used in this study is convenience sampling, a non-random sampling technique. Primary data was used and collected through distributing questionnaires to 120 SMEs. The findings of this study are that the UTAUT Model, namely performance expectations, effort expectations, and social influences, has an influence on interest in using an information system. The facilitating conditions and SMEs' interest in using information systems will ultimately influence them to accept and use information systems to support their business activities.